Dermal exposure to cobalt studied in vitro in keratinocytes – effects of cobalt exposure on inflammasome activated cytokines, and mRNA response. (17th November 2021) - Klasson, Maria; Lindberg, Magnus; Westberg, Håkan; Bryngelsson, Ing-Liss; Tuerxun, Kedeye; Persson, Alexander; Särndahl, Eva
Abstract: Background: Cobalt is a dermal sensitizer, and keratinocytes respond to cobalt exposure by releasing proinflammatory mediators, regulating the immune response. Objective: To determine the effect of cobalt on the inflammasome associated cytokine- and gene expression in cultured human keratinocytes (HaCaT). Cultivation in low- or high calcium conditions model separate differentiation states of keratinocytes in the skin. Method: HaCaT cells in two different states of differentiation were exposed to cobalt chloride and caspase-1 activity as well as the production of IL-1β, IL-18 and gene expression of IL1B, IL18, NLRP3, CASP1, and PYCARD was quantified. Results: High cobalt chloride exposure mediated significant increase in caspase-1 activity, cytokine levels, and IL1B and NLRP3 expression with a corresponding regulatory decrease for CASP1 and PYCARD expression. No difference between high- and low calcium culturing conditions modelling differentiation states was detected. Conclusions: Our data suggest that HaCaT cells respond with inflammmasome associated activity upon cobalt exposure in a concentration-dependent manner. These mechanisms could be of importance for the understanding of the pathophysiology behind allergic sensitization to dermal cobalt exposure.